2014
DOI: 10.2320/matertrans.md201310
|View full text |Cite
|
Sign up to set email alerts
|

Development of TEM Holder Generating In-Plane Magnetic Field Used for <i>In-Situ</i> TEM Observation

Abstract: For easy performance of Lorentz microscopy with simultaneous electric measurements, a special specimen holder for transmission electron microscopy (TEM) has been developed that has electromagnets to generate magnetic field and four leads for electric measurements. This TEM holder was evaluated by checking experimental results of permalloy (Ni 0.8 Fe 0.2 ) patterns. Clear observations of domain wall injection into a nanowire and movement of magnetic vortices as well as magnetoresitance during the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…A number of approaches have been proposed, including tilting the sample into the field of the objective lens or using a sample holder to which small electromagnets are mounted. Further sophistication can be achieved by combining application of a magnetic field with application of current, as shown by Arita et al [10] who showed the use of LTEM to image domain walls injected into Permalloy wires using a holder that they had developed. One of the issues associated with in situ applied fields is deflection of the incident electron beam, and although the holder developed by Arita et al is limited to an applied field of ±200 Oe, an advantage of its design is that the deflection of the electron beam by the applied field is compensated by a second set of magnetizing coils mounted on the holder.…”
Section: Imaging Magnetization Reversal Behaviormentioning
confidence: 99%
“…A number of approaches have been proposed, including tilting the sample into the field of the objective lens or using a sample holder to which small electromagnets are mounted. Further sophistication can be achieved by combining application of a magnetic field with application of current, as shown by Arita et al [10] who showed the use of LTEM to image domain walls injected into Permalloy wires using a holder that they had developed. One of the issues associated with in situ applied fields is deflection of the incident electron beam, and although the holder developed by Arita et al is limited to an applied field of ±200 Oe, an advantage of its design is that the deflection of the electron beam by the applied field is compensated by a second set of magnetizing coils mounted on the holder.…”
Section: Imaging Magnetization Reversal Behaviormentioning
confidence: 99%
“…However, due to the deflection of electron trajectories by magnetic fields, these techniques do not easily allow for the application of an in-plane magnetic field 18 .…”
mentioning
confidence: 99%
“…This procedure just requires a set of ending states produced by reversing the magnetization. The maximum pulsed magnetic field of 415 kA/m is larger than those of less 72 kA/m in the previously developed magnetization systems placed on 26 , 27 and around 12 , 28 the sample holder, which were designed to perform in-situ observation of the magnetic behaviour in a steady applied magnetic field. The developed system can be widely used to reverse the magnetization in hard magnets or magnets with a large shape effect, as demonstrated in a thin oxide magnet by applying a 207-kA/m pulsed magnetic field (Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%